Effects of the Interface Properties on the Performance of UV-C Photoresistors: Gallium Oxide as Case Study - Maura Pavesi; Antonella Parisini; Pietro Calvi; Alessio Bosio; Roberto Fornari (Sensors)
Electrical contacts are of the greatest importance as they decisively contribute to the overall performance of photoresistors. Undoped κ-Ga2O3 is an ideal material for photoresistors with high performance in the UV-C spectral region thanks to its intrinsic solar blindness and extremely low dark current. The quality assessment of the contact/κ-Ga2O3 interface is therefore of paramount importance. The transfer length method is not applicable to undoped Ga2O3 because the interface with several metals shows a non-ohmic character, and a non-equivalent contact resistance could restrict its applicability. In this work, a new methodological procedure to evaluate the quality of contact interface and its effect on the sensing performance of UV-C photoresistors is presented, using the SnO2−x/κ-Ga2O3 contact interface as a case study. The proposed method includes a critical comparison between two-point and four-point probe measurements, over a wide range of voltages. The investigation showed that the effect of contact resistance is more pronounced at low voltages. The presented method can be easily extended to any kind of metal/semiconductor or degenerate-semiconductor/semiconductor interface.